Susceptibility to COVID-19 Negatively Associated with Parental Consanguineous Marriage, A Case-Control Study - Saadat, Mostafa; Zolaadl, Mohammad Hossein; Asadollahi, Abdolrahim (Jordan Medical Journal, 2024)
Background: Marriage between biological relatives (second cousins and closer relatives) is called consanguineous marriage. Autosomal recessive diseases and several multifactorial traits are increased in the offspring of consanguineous marriages. Aim: To investigate the relationship between parental consanguinity and COVID-19 susceptibility in their offspring, the present study was performed. Methods: A total of 302 confirmed COVID-19 patients and 304 participants with other disease (as controls) were included in the study. Data on age, type of parental marriage, educational level, and history of underlying diseases of the participants were collected by a simple questionnaire through an interview conducted by a general practitioner. Results: Statistical analysis showed that parental consanguinity was negatively associated with the risk of COVID-19 (OR=0.66, 95% CI=0.44-0.98, P=0.041). Using multivariable logistic regression analysis, parental consanguineous marriages significantly decreased the risk of COVID-19 after adjusting for age, education level, and the presence of underlying diseases such as diagnosed cardiovascular disease, hypertension, diabetes mellitus, and cancer (OR=0.60, 95% CI=0.40-0.90, P=0.014). Conclusions: The present finding means that offspring of consanguineous marriages had a lower risk of COVID-19 than offspring of unrelated marriages.